Potentiometric titration of P-anisidine and P-toluidine in non-aqueous media - Kocaoba, Sevgi; Aydogan, Feray; Afsar, Huseyin (FREUND PUBLISHING HOUSE LTD, 2006)
Potentiometric titrations of p-anisidine and p-toluidine were carried out with hydrochloric acid in toluene solvent. The same titrations were done with hydrochloric acid in methanol solvent to show the effect of amphiprotic solvent in the titrations with hydrochloric acid. For each weak base, an S-shaped potentiometric titration curve was obtained. As a result, toluene, which is an aprotic inert solvent, is a suitable solvent for titrating some of the weak bases potentiometrically.
Keywords: non-aqueous titrations; toluen; hydrochloric acid; p-anisidine; p-toluidine; TETRABUTYLAMMONIUM HYDROXIDE; NITROBENZENE SOLVENT; ACIDS; ACETONITRILE; AMINES; Chemistry